The influence of the precipitation recycling process on the shift to heavy precipitation over the Tibetan Plateau in the summer - Zhang, Boyuan; He, Yongli; Ren, Yu; Huang, Bo; Peng, Yangrui; Wang, Shanshan; Guan, Xiaodan (Frontiers in Earth Science, 2023)
On the Tibetan Plateau (TP), precipitation intensity has shifted to heavy precipitation due to global warming. However, the influence of the precipitation recycling process on this phenomenon remains unknown. Using the Water Accounting Model-2layers (WAM2layers) model and ERA5 reanalysis, this study investigates the contributions of the precipitation recycling process to precipitation shifts over the TP during 1979-2019. The precipitation shift rate was proposed to quantify this process, and the results reveal that the positive precipitation shift (1.384 mm/41 years) over the TP consists of a positive shift over the western TP (5.666 mm/41 years) and a negative shift (-3.485 mm/41 years) over the eastern TP. Considering the source of moisture, either a local source or a remote source, precipitation was decomposed into internal and external cycles of the precipitation recycling process based on the WAM2layers model. Further analysis indicates that the internal cycle (87.2%) contributes more to the shift than the external cycle (12.8%) over the TP. The contributions of the precipitation recycling ratio (PRR) and precipitation amount to the precipitation shift rate induced by the internal cycle were further investigated. The results indicate that PRR changes contribute more to heavy precipitation over the TP, while precipitation amount changes contribute more to light precipitation. The precipitation recycling process contributes to the shift by increasing atmospheric moisture and increasing (decreasing) the dependency on local evaporation in heavy (light) precipitation. Increased dependence of heavy precipitation on evaporation increases the risk of extreme precipitation, and the government should take preventative actions to mitigate these adverse effects.